PENGARUH ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN, DAN INOVASI TERHADAP KINERJA PEMASARAN (STUDI KASUS PADA UMKM KERAJINAN LOGAM DI KABUPATEN TEGAL) - Amrulloh, Fajrin; Hidayat, Wahyu (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
In business competition, Small and Medium Enterprises (SMEs) are required to have dynamic capabilities and strategies that capture opportunities and renew markets and improve marketing performance through the creation of marketable and profitable products on an ongoing basis. Strategies that can be done in the form of market orientation, and entrepreneurial orientation so as to encourage the creation of innovation. This research is conducted to determine the influence of market orientation, entreprenual orientation and innovation toward marketing performance in Metal Craft SMEs of Tegal Regency. This type of research is explanatory research. The sampling technique used total sampling that is overall Metal Craft SMEs owner of Tegal Regency. The respondents in this research totaled 40 respondents. Collecting data used questioner by using Likert measurement scale. This research also using Path analysis tecniques supported by SPSS (Statistical Package for Social Science) software version 22.0. the validity test, reliability test, chross tab, coefficient of correlation, coefficient of determination test, linier and multiple regression, significance test ( t and F test) and Sobel method before hand. The result showed tha all independent variables in this study had a positif influence and significant on the dependent variable, either partially or simultaneous, innovation acts as a partial mediating variable, that indicates an indirect effect of market orientation and entrepreneurial on marketing performance.